Examining the Impact of Digital Economy on Consumer Preferences in the Metaverse Era: An Empirical Study on the Role of NFTs and Tokenization in Changing Purchase Intentions - Agung Wijoyo (Golden Ratio of Data in Summary, 2024)
This study aims to investigate the impact of the digital economy on consumer preferences in the Metaverse era, focusing on the role of Non-Fungible Tokens (NFTs) and tokenization in changing purchase intentions. Using a mixed-methods approach, this study combines quantitative and qualitative analysis to gain a comprehensive understanding of the key determinants of consumer purchase intentions in a rapidly evolving digital context. The results of the quantitative analysis show that perceived value, trust in blockchain technology, and user experience significantly influence consumer purchase intentions towards NFTs. Qualitative analysis through in-depth interviews reveals that scarcity, digital ownership, and community involvement are the main factors driving NFT adoption, while lack of technological understanding and regulatory uncertainty are the main barriers. This study also introduces novelty through the use of machine learning-based sentiment analysis and social network analysis to explore the role of social interactions in the formation of purchase intentions. These findings make important contributions to the literature on the digital economy by offering new insights into consumer dynamics in the Metaverse and highlighting the need for marketing strategies that focus on creating community value and immersive user experiences. Practical implications of this study include the need for consumer education and clear regulations to increase NFT adoption, as well as marketing strategies that leverage the emotional value and scarcity of digital assets. This research contributes to a better understanding of consumer behavior in the digital age and offers recommendations for further research in this area.